A comparative analysis of methylome profiles of Campylobacter jejuni sheep abortion isolate and gastroenteric strains using PacBio data - Mou, Kathy T.; Muppirala, Usha K.; Severin, Andrew J.; Clark, Tyson A.; Boitano, Matthew; Plummer, Paul J. (Frontiers in Microbiology, 2015)
Campylobacter jejuni is a leading cause of human gastrointestinal disease and small ruminant abortions in the United States. The recent emergence of a highly virulent, tetracycline-resistant C. jejuni subsp. jejuni sheep abortion clone (clone SA) in the United States, and that strain’s association with human disease, has resulted in a heightened awareness of the zoonotic potential of this organism. Pacific Biosciences’ Single Molecule, Real-Time sequencing technology was used to explore the variation in the genome-wide methylation patterns of the abortifacient clone SA (IA3902) and phenotypically distinct gastrointestinal-specific C. jejuni strains (NCTC 11168 and 81-176). Several notable differences were discovered that distinguished the methylome of IA3902 from that of 11168 and 81-176: identification of motifs novel to IA3902, genome-specific hypo- and hypermethylated regions, strain level variability in genes methylated, and differences in the types of methylation motifs present in each strain. These observations suggest a possible role of methylation in the contrasting disease presentations of these three C. jejuni strains. In addition, the methylation profiles between IA3902 and a luxS mutant were explored to determine if variations in methylation patterns could be identified that might explain the role of LuxS-dependent methyl recycling in IA3902 abortifacient potential.